Endoscopic removal of a battery that was lodged in the oesophagus of a two-year-old boy for an extremely long time - Szaflarska-Popławska, Anna; Popławski, Cezary; Romańczuk, Bartosz; Parzęcka, Monika (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
In the present work we describe a 2-year-old boy whose battery ingestion was overlooked, and who had the battery endoscopically removed from the upper part of his oesophagus after several months. This is the only described case of such a long impaction of a lithium battery in the oesophagus, without development of severe complications. We stress the necessity to take into account ingestion of a dangerous foreign body by children demonstrating unspecific clinical signs.